PENGARUH SOCIAL COMPARISON TERHADAP BODY IMAGE REMAJA AKHIR LAKI-LAKI DI SMAN 1 KAKAS - Ferendita S. Manatar; Tellma M. tiwa; Dewo A. N. Narosaputra (Program Studi Psikologi Universitas Negeri Manado, 2022)
This study aims to determine the effect of social comparison on body image in late adolescent boys at SMAN 1 Kakas. This research method uses quantitative methods. The subjects of this study were 153 late adolescent boys at SMAN 1 Kakas with a non-probability sampling technique using purposive sampling. The research instruments used in this study were the PACS-R (2014) scale which measures social comparison and BAS-2 (2015) which measures body image. The research results were tested using a simple regression analysis. The results of the analysis show that there is a significant positive effect of social comparison on body image in late adolescent boys at SMAN 1 Kakas with the resulting social comparison effect of 89%. Based on the hypothesis test, it is concluded that H1 is accepted, meaning that Social Comparison has a negative and significant effect on Body Image.